Etiological and Clinical Patterns of Isolated Hepatomegaly at a Tertiary Level Hospital in Bangladesh - Chanchal Kumar Ghosh; Fakhrul Islam; Ershaduddin Ahmed; Dilip Kumar Ghosh; Azizul Haque; Q. T. Islam; M. A. Azhar (Recent Developments in Medicine and Medical Research Vol. 1, 2021)
The aim of the study was to find out the etiology of isolated hepatomegaly in Bangladesh. A prospective cross sectional study was done at medicine department in a tertiary care hospital in Bangladesh. Consecutive one hundred hospital admitted patients having isolated hepatomegaly were included in the study. Hepatomegaly is usually associated with splenomegaly. However, sometimes there may be isolated hepatomegaly without splenomegaly in different pathological conditions. In our study we found that most common cause of isolated hepatomegaly was liver abscess (34.0%) followed by congestive cardiac failure (30.0%), Viral hepatitis (14%), secondaries in the liver ( 8%) primary hepatocellular carcinoma( 6%) and Fatty liver (2%). Among the liver abscess 59% were amebic & 41% were pyogenic abscess.